Brain activity changes associated with pain perception variability. (7th September 2022) - Crawford, L; Mills, E; Meylakh, N; Macey, P M; Macefield, V G; Henderson, L A
Abstract: Pain perception can be modulated by several factors. Phenomena like temporal summation leads to increased perceived pain, whereas behavioral conditioning can result in analgesic responses. Furthermore, during repeated, identical noxious stimuli, pain intensity can vary greatly in some individuals. Understanding these variations is important, given the increase in investigations that assume stable baseline pain for accurate response profiles, such as studies of analgesic mechanisms. We utilized functional magnetic resonance imaging to examine the differences in neural circuitry between individuals displaying consistent pain ratings and those who experienced variable pain during a series of identical noxious stimuli. We investigated 63 healthy participants: 31 were assigned to a "consistent" group, and 32 were assigned to a "variable" group dependent on pain rating variability. Variable pain ratings were associated with reduced signal intensity in the dorsolateral prefrontal cortex (dlPFC). Furthermore, the dlPFC connectivity with the primary somatosensory cortex and temperoparietal junction was significantly reduced in variable participants. Our results suggest that investigators should consider variability of baseline pain when investigating pain modulatory paradigms. Additionally, individuals with consistent and variable pain ratings differ in their dlPFC activity and connectivity with pain-sensitive regions during noxious stimulation, possibly reflecting the differences in attentional processing and catastrophizing during pain.